Enhancement of tribological behaviour and thermophysical properties of engine oil lubricant by Graphene/Co-Cr nanoparticle additives for preparation of stable nanolubricant. Issue 1 (February 2021) - Sandhya, M; Ramasamy, D; Kadirgama, K; Harun, W S W; Samykano, M; Ameer, A
Abstract: In the current study the tribological properties of Aluminum alloy (Al 25) with moment in time was examined by adding nanoparticles as additives. Nanoparticles exhibit high thermal conductivity, stable viscosity and can be dispersed well in oil. The purpose of this research is to determine the effect of Al2 O3, TiO2, Graphene (G), Co-Cr, Ni nanoparticles on lubricity using linear wear testers under reciprocating sliding motion. SEM and EDX characterization techniques are used to study the composition and morphology on worn surfaces. The findings showed that the tribological properties of the substrate lubricant were significantly increased with the addition of nanoparticles. Friction and Wear are reduced with Graphene, Al2 O3, TiO2, Ni & Co-Cr nanoparticles as additives for the same load value and can be used as multifunctional additives. Co-Cr at 0.03wt% has provided best performance among the other nanoparticles and can be used as Nano lubricant in the future.